The EFL Learners’ Perspectives on the Online English Course Conducted through WhatsApp Group Interactions - effi wahyuningsih (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2020)
This study aims at highlightingthe EFL learners’ perspectives on Kulwap– online English course conducted through WhatsApp Group Interactions.This is an exploratory research project employing a qualitative method. The data of the study were gained through informal semi-structured interview and students’ written testimonies. The research findings show that conducting English online course through kulwap proposes advantages as well as challenges that must be consider for the future instructional process. The benefits of Kulwap include the accessibility, simplicity, convenience, and flexibility the students got during the instructional process if English course. On the other hand, the challenges faced by the students regarding the online course through Kulwap cover the problems of internet connectivity, and other technical things including the eye strain, students’ lack motivation, and limited response from the lecturer during the online instructional process.